Synthesis of cyclic carbonates by addition of CO2 to epoxides at atmospheric pressure - Fawaz Al Hussein; Julen Larrucea; Nicolás Otero; Andreas Hartwig; Henning Großekappenberg (Journal of CO2 Utilization)
The fixation of carbon dioxide (CO2) is a critical challenge for the sustainable synthesis of chemical compounds. This study presents a highly effective catalytic system for the synthesis of cyclic carbonates through the fixation of CO2 on epoxides. The system is designed for ease of use, facilitated by the industrial-scale availability of the compounds and the moderate reaction conditions. The catalyst system employs tertiary amines in conjunction with halogenated alkali metal salts. Detailed kinetic studies of the cycloaddition reaction between epoxides and CO2 were conducted using NMR spectroscopy. The reaction mechanism was thoroughly investigated and elucidated. The catalyst system demonstrates high efficacy with different kind of epoxides achieving high yields (>90 %) and high selectivity (>90 %). Notably, the entire process is conducted without solvents and at ambient pressure, highlighting its significant ecological benefits.